2012
DOI: 10.1002/cncr.27508
|View full text |Cite
|
Sign up to set email alerts
|

Insurance and inpatient care

Abstract: BACKGROUND: Early research demonstrated that patients' length-of-stay and inpatient costs varied according to their health insurance status. The authors of the current report studied a population-based sample of privately insured, Medicaid-insured, and uninsured inpatients ages 21 to 64 years who underwent surgical resection for either nonsmall cell lung cancer (NSCLC) (n ¼ 781) or colorectal cancer (CRC) (n ¼ 8190) or who underwent mastectomy (n ¼ 6201) to compare length of stay and inpatient costs by insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The main strength of this study is the use of a nationwide population-based dataset from Taiwan which launched a universal NHI program that covered more than 99% of its population. Therefore this study excluded the influence of insurance status which had been demonstrated to be an important confounding factor influencing the care of patients with colon cancer 27 . At the time of the sampling period, laparoscopic surgery for colon cancer has become a mature technique.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this study is the use of a nationwide population-based dataset from Taiwan which launched a universal NHI program that covered more than 99% of its population. Therefore this study excluded the influence of insurance status which had been demonstrated to be an important confounding factor influencing the care of patients with colon cancer 27 . At the time of the sampling period, laparoscopic surgery for colon cancer has become a mature technique.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this study is the usage of a nationwide population-based dataset from Taiwan which launched a universal NHI program at the end of 1995, and NHI program covered 98 % of Taiwan’s population. This study therefore excluded the influence of insurance status from our analysis which was demonstrated as an important factor influencing care of patients with colon cancer [ 34 ]. However, there are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous national studies of Medicaid patients undergoing surgery have shown worse outcomes 2 and increased costs. 3 Given the ACA also mandates a reduction in payments to disproportionate share hospitals (DSH), 4 increased Medicaid enrollment could have substantial clinical and financial implications for hospitals facing expansion. To better understand this change, we examined the surgical outcomes and resource use of Medicaid patients in Michigan the year prior to implementation of the ACA using a statewide clinical registry.…”
mentioning
confidence: 99%